ANALYZING THE IMPACT OF RESEARCH AND COMMUNITY SERVICE PROGRAMS OF HIGHER EDUCATION INSTITUTIONS ON LOCAL ECONOMIC EMPOWERMENT ININDONESIA: A LITERATURE REVIEW STUDY - Togi Adnan; Nunuk Praptiningsih; Nawang Kalbuana (Adisam Publisher, 2024)
This literature review delves into the intricate dynamics of higher education institutions' research and community service programs and their impact on local economic empowerment in Indonesia. By synthesizing a diverse array of scholarly articles, case studies, and reports, this study comprehensively examines the multifaceted contributions made by higher education to the economic development of local communities. Key themes explored encompass knowledge transfer, technology diffusion, and the holistic engagement of community service initiatives. The review underscores the transformative potential of collaborative efforts between academia, local governments, and businesses. However, it also identifies critical gaps, including geographical biases and limited assessments of long-term sustainability. This synthesis contributes valuable insights for policymakers and academia, offering recommendations to enhance the effectiveness of higher education programs in fostering sustainable economic empowerment at the local level in the Indonesian context.